Call the nurse : true stories of a country nurse on a Scottish isle - MacLeod, Mary J. (New York : Arcade Publishing, 2013)
The author recalls her time living and working as a nurse on a remote island in the Scottish Hebrides.
Keywords: MacLeod, Mary J. -- Career in nursing; Nurses -- Scotland -- Hebrides -- Biography; Nursing -- Scotland -- Hebrides -- History; Hebrides (Scotland) -- Social life and customs